Kompleksitas Approach dan Eksistensi Pendidik - Yustizar; Rasyid, Muhammad Nuh (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2022)
A child is born in a state of "sacred" nature and has the potential to be intelligent and successful in the future, just like an animal that is continuously trained, it becomes intelligent, different from its community. Likewise with humans who are bestowed with perfection in the creation of the creator. Educated humans will certainly influence the success of life, meaning that success or not in life can be influenced by the pattern of students who originate either in the family environment, home environment or school environment. Parents are teachers for children, while educational institution teachers serve as a counterbalance to the curriculum as a structure of knowledge in the child. There are often social complaints about "failure". The excuse for failure of educators or approaches in educating. This is what has the complexity of being studied in scientific discussions which then becomes criticism of the world of education itself. The compulsion towards education began to be packaged again with the term trend approach (approach).